Penyusunan Rencana Strategis Rumah Sakit Pertamina Jaya Tahun 2017-2022 - Karmawan, Budi (UI Scholars Hub, 2016)
The focus of this study is how to develop strategic planning for hospitals, with case studies of Pertamina Jaya Hospital which is a class C private hospital. This research is qualitative research with descriptive design. The results showed that environmental factors both external as well as internal hospital put the Pertamina Jaya Hospital on the position of Growth and Build on IE Matrix and Internal Fix-It on TOWS Matrix. An alternative strategy is doing market penetration accompanied improvements in hospital weaknesses to capture opportunities. Implementation plan was drawn up in order to be in line with the achievement of Hospital Vision to be come a Healthcare Organization which can compete in the era of globalization with International-standard Services by 2020.